PERFORMANCE ANALYSIS OF INVESTIGATORS IN UNCOVERING CYBER FRAUD: (Case Study at the West Jakarta Metro Police) - Joshua Oktavianus Siagian; Surya Nita; Aldika Martua Sitorus; Riska Sri Handayani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The aim of this study is to evaluate the performance of investigators in handling cybercrime cases in the jurisdiction of West Jakarta Metro Police. The research method used is literature review and secondary data analysis from various reliable sources regarding the development of information technology and cybercrime in Indonesia. The research results show that Investigators in the Cybercrime Subunit of West Jakarta Metro Police have shown significant efforts in handling cybercrime cases, especially cyber fraud. They have utilized various investigation methods and techniques in accordance with the applicable laws in Indonesia, including the ITE Law and other related regulations. However, investigators face several challenges, including limited facilities and infrastructure such as inadequate computers and other devices. Budget constraints are also a major obstacle, especially in funding investigative operations outside Jakarta. In addition, poorly organized SOPs and lack of consistency in their implementation also hinder the effectiveness of investigations. This includes inconsistencies in delivering SP2HP in accordance with Perkap Number 14 of 2012. The implementation of information technology, such as Smart Policing and E-SP2HP programs, has helped improve personnel capacity and real-time reporting. However, further evaluation is needed to ensure the effectiveness and integration of this technology with the coordination of relevant institutions. Success in handling cybercrime also depends on cooperation among law enforcement agencies and increased training for cyber police officers. This includes establishing guidelines for handling cybercrime cases and adopting effective digital forensic methods.